Work hours, weekend working, nonstandard work schedules and sleep quantity and quality: findings from the UK household longitudinal study - Gillian Weston; Afshin Zilanawala; Elizabeth Webb; Livia Carvalho; Anne McMunn (BMC, 2024)
Abstract Background Atypical temporal work patterns such as working longer than the standard 35-40 h/ week, weekend working, and nonstandard work schedules (i.e. outside of the typical 9-5, including but not restricted to shiftwork) are increasingly prevalent in the UK. Aside from occupation-specific studies, little is known about the effects of these atypical temporal work patterns on sleep among workers in the UK, even though poor sleep has been linked to adverse health problems, lower workplace productivity, and economic costs. Method We used regression models to investigate associations between three types of atypical temporal work patterns (long and short weekly work hours, weekend working, and nonstandard schedules) and sleep duration and disturbance using data from over 25,000 employed men and women from 2012-2014 and/or 2015-2017 in the UK Household Longitudinal Study, adjusting for potential confounders and psychosocial work factors. Results We found that relative to a standard 35-40 h/week, working 55 h/week or more was related to short sleep (less than 7 h/night) and sleep disturbance. Working most/all weekends compared to non-weekends was associated with short sleep, long sleep (more than 8 h/night), and sleep disturbance, as was working nonstandard schedules relative to standard schedules (fixed day-time schedules). Further analyses suggested some gender differences. Conclusions These results should prompt employers and policymakers to recognise the need for rest and recovery, consider how the timing and scheduling of work might be improved to better support workers' health and productivity, and consider appropriate compensation for anyone required to work atypical temporal work patterns.